(3GdJHUQIs - (3YHO Gddg Hf jhSa Hf eMeO Hf Mjhjg GdLhjfj, CHh eMeO,J (B438 (3g` s ((3cjcdOi Hf YHO Gddg s)
(3ChdgG (B:s
(3GdMeO ddg Ydi ShGHb fYeGFg hShGda BdGFg CeG HYO aEf Gddg SHMGfg GNHQfG ai Mce cJGHg hbGd dfG Ef GdTjWGf dce YOh aGJNPhg YOhkG s
(3BNQgG (B:s
(3hEPG cGf EjVGM GdSQGQi Ydi gPg GdLgI aGdGMJjGW ai YUQfG GLJfGHgf eedhcGJ hMQGFQ hGddg CYde hgh Gdehab ddUhGH BNQ cJGH GdJHUQI s
(3GdhQbJGf GdChdjGf HNW MOjKs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B165s
Keywords: (3Gdabg GdTGaYjs